Patient experience of negative pressure wound therapy: A qualitative study - Aiko Miyanaga; Toru Miyanaga; Keiko Sakai; Chizuko Konya; Kimi Asano; Kenichi Shimada (Wiley, 2023)
Abstract Aim This study aimed to clarify the treatment experience of patients undergoing negative pressure wound therapy (NPWT). Design This study used a qualitative design. Methods Seventeen inpatients were semi‐structured interviewed about their experiences of treatment with negative pressure wound therapy. Results Inpatients' answers were categorized into seven themes: pain and discomfort associated with treatment, physical limitations owing to attached device, mental burden owing to the odour and noises of the attached device, social limitations owing to the attached device, advances in medical care and science, device personification and mixed feelings towards medical staff. The patients were able to tolerate the aforementioned limitations while feeling attachment and gratitude towards the device created through advances in medical care and science, and towards medical staff who helped them heal. In the future, we plan to develop an NPWT care guide.